Frequency of Non-Alcoholic Fatty Liver Disease in Patient with Chronic Kidney Disease - Ahmed, Saghir (Indus Journal of Bioscience Research, 2025)
Background: Non-alcoholic fatty liver disease (NAFLD) is increasingly recognized as a major comorbidity in patients with chronic kidney disease (CKD). Both conditions share common risk factors, including obesity, diabetes, hypertension, and dyslipidemia. Early detection of NAFLD in CKD patients is crucial for preventing progression of both hepatic and renal dysfunction. Objectives: To determine the frequency of non-alcoholic fatty liver disease among patients with chronic kidney disease and to evaluate its association with clinical parameters and biochemical abnormalities. Study Design: A cross-sectional study. Place and Duration of study: Department of General Medicine, Bolan Medical Complex Hospital, Quetta, from December 2023 to June 2024. Methods: A cross-sectional study was conducted among 142 patients with confirmed CKD attending the nephrology outpatient department. NAFLD was diagnosed using abdominal ultrasonography after excluding alcohol intake and other hepatic causes. Relevant biochemical and clinical data were collected, including body mass index, fasting glucose, and lipid profile. Statistical analysis was performed using SPSS version 24.0, with p < 0.05 considered significant. Results: Among 142 CKD patients (mean age = 52.4 ± 11.2 years), 82 (57.7%) were males and 60 (42.3%) females. NAFLD was detected in 81 patients (57.0%). Patients with NAFLD had significantly higher mean body mass index (28.6 ± 3.9 kg/m² vs 25.2 ± 3.6 kg/m², p = 0.001) and serum triglycerides (186.4 ± 42.5 mg/dL vs 148.3 ± 38.1 mg/dL, p = 0.002). Elevated fasting glucose and alanine transaminase levels were also more prevalent among NAFLD patients (p < 0.05). The frequency increased with higher CKD stages. Conclusion: Non-alcoholic fatty liver disease was highly prevalent among patients with chronic kidney disease, particularly those with obesity and metabolic abnormalities. The significant association between NAFLD and advanced CKD underscores the need for routine hepatic evaluation and metabolic control in renal patients. Early diagnosis and management may help reduce disease progression and improve overall outcomes in this high-risk population.